Wisata Hutan Bakau Kampung Kelembak - Hanjaya, Jonathan; Suwarlan, Stivani Ayuning; Victoria, Victoria; Tjandra, Sherrin; Audrey, Audrey; Diani, Diani; Kristin, Kristin; Sarinah, Sarinah; Herianto, Herianto; Kelly, Kelly (National Conference for Community Service Project (NaCosPro), 2019)
Kelembak Village is a village located in Nongsa District that has potential and value to be a tourism area for local people and foreign tourists called Kelembak Cultural Tourism Village, where will be a tourist village with Malay culture in the 1960s era. The area of ??Kelembak Village which is being developed into a tourism area is 6 hectares and the locations for the development of tourist area had been determined by residents but they do not have a tourist map to guide visitors on a tour and the purpose of the social activity is to make a Kelembak Village map as a guide for local people and foreign tourist.